Mekanisme Mempertahankan Teritori dalam Suatu Wilayah - Parmonangan Manurung; Ikaputra Ikaputra (Diponegoro University, 2020)
Territoriality is a term that was initially used to describe the realm of power in animals, especially birds. In its development, this terminology is also used to define areas owned by humans, both individuals, and groups. This study aims to find the process and mechanism of forming territorial areas in built environments, as well as the defense system used, both on a micro and macro scale. The study was conducted using a content analysis method with the object of research being various texts related to